The first molecular phylogeny of Chilodontidae (Teleostei: Ostariophysi: Characiformes) reveals cryptic biodiversity and taxonomic uncertainty - Melo, Bruno F. [UNESP]; Sidlauskas, Brian L.; Hoekzema, Kendra; Vari, Richard P.; Oliveira, Claudio [UNESP] (Elsevier B.V., 2014)
Chilodontidae is a small family of eight described characiform species popularly known as headstanders. These small to moderately sized fishes are well known to aquarists, who prize their striking spotted pigmentation and unusual behaviors, and to systematists, who have revised both chilodontid genera in recent memory and studied their phylogenetic relationships using a comprehensive morphological dataset. However, no molecular phylogeny for the family has ever been proposed. Here, we reconstruct phylogenetic relationships for all eight known chilodontid species using three mitochondrial and two nuclear loci. Results largely agree with the previous morphological hypothesis, and confirm the monophyly of the family as well as its included genera, Caenotropus and Chilodus. The molecular topology differs slightly from the morphological hypothesis by placing Caenotropus maculosus rather than C. mestomorgmatos as the sister to the remaining three congeners, and by reconstructing the Curimatidae as the closest out-group family, rather than the Anostomidae. However, the topologies supported by the morphological data were only slightly less likely and could not be rejected via Shimodaira-Hasegawa tests. Within Chilodus, two described species with distinctive pigmentation (C fritillus and C zunevei) appear embedded within the broad distributed C. punctatus clade, suggesting the presence of cryptic taxa with polymorphic pigmentation within the present concept of C punctatus. Future work should combine morphological and molecular data to revisit the taxonomy and systematics of Chilodus and determine species limits within the C punctatus-group sensu lato. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Amazon; Freshwater fishes; Headstanders; Multilocus analysis; Systematics